EVALUATION OF KERATOCYSTIC ODONTOGENIC TUMORS USING CONE BEAM COMPUTED TOMOGRAPHY - Mustafa Gümüşok; Meryem Toraman Alkurt; Farid Museyibov; Özlem Üçok (Istanbul University, 2016)
Purpose: The aim of this retrospective study is to determine the radiological features of keratocystic odontogenic tumors (KCOT) using cone-beam computed tomography (CBCT).Materials and Methods: CBCT images of 28 patients who had histopathologically-confirmed KCOT were retrospectively reviewed from the archives of the Department of Dentomaxillofacial Radiology, Gazi University Faculty of Dentistry. The location and size of KCOT, cortical expansion, cortical perforation, relation with the impacted teeth, and the impact on the mandibular canal were evaluated. Results: The mean age of patients at initial diagnosis was 34.5 years. Patients with an impacted tooth were significantly younger than those without an impacted tooth (p<0.05). Among KCOTs, 21% were localized in the maxilla whereas 79% were found in the mandible. The lesions localized in the mandible were mostly found in the retromolar-ramus region. Of these patients, 93% had cortical expansion and 75% had bone perforation. Of the 22 mandibular lesions, 20 were in close proximity of the mandibular canal and 18 (90%) of these lesions had caused destruction in the mandibular canal. Conclusion: KCOTs exhibit their aggressive nature in the jaw bone. CBCT is a useful radiological imaging method to examine the radiologic characteristics of KCOTs such as bone destruction and their spatial relations with the neighboring anatomic structures.